2006
DOI: 10.1207/s15430154jce2103_14
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer Prevention and Early Detection: Knowledge, Practices, and Opinions of Oral Health Care Providers in New York State

Abstract: Background-The purpose of this study was to assess the knowledge, practices, and opinions of dentists and dental hygienists in New York State regarding oral cancer prevention and early detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
2
26

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(108 citation statements)
references
References 21 publications
8
72
2
26
Order By: Relevance
“…A variation in the knowledge of dental health care professionals and their opinions and practices regarding oral cancer prevention and early detection has been described in numerous surveys in the USA ; Maryland ; Texas (Alonge and Narendran, 2003); Brazil (Leao et al, 2005); New York (Gajendra et al, 2006) ; the UK ; Canada (Clovis et al, 2002);…”
Section: Epidemiological Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…A variation in the knowledge of dental health care professionals and their opinions and practices regarding oral cancer prevention and early detection has been described in numerous surveys in the USA ; Maryland ; Texas (Alonge and Narendran, 2003); Brazil (Leao et al, 2005); New York (Gajendra et al, 2006) ; the UK ; Canada (Clovis et al, 2002);…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…Ireland (Decuseara et al, 2011);Spain (López-Jornet et al, 2011) and Italy (Colella and Gaeta, 2008 A study conducted in New York State among a random sample of practicing dentists and dental hygienists found them to be knowledgeable about oral cancer, but with gaps in the knowledge related to the risk factors and in oral cancer examination techniques (Gajendra et al, 2006). López-Jornet et al (2011) conducted a postal survey among a random selection of general dentists in Spain and also found that gaps in knowledge that strongly suggested the need for continued education courses in the detection and prevention of oral cancer (López-Jornet et al, 2011).…”
Section: Epidemiological Studiesmentioning
confidence: 99%
See 3 more Smart Citations